Legal Measures to Control Alcoholic Beverages Advertising on the Internet - sukperm, kritiya; Barisri, Jirapon (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2020)
Legal measures to control alcoholic beverages advertising on the Internet. The Study the concept in controlling alcoholic advertising and analyze problems, propose guidelines for legal measures to control alcoholic beverages advertising on the Internet. The study found that advertising of alcoholic beverages is an important marketing strategy for alcohol drinking business operators. That will increase the sales of alcohol drinking and help stimulate demand for alcohol drinking. The using internet media as alcohol advertising such as Facebook Instagram and Line as a way to communicate with the target group who receive quick feedback and spread widely. The law still cannot control the advertising of alcoholic beverages on the internet. The research suggested that the alcoholic beverage marketing and advertising measures should be set according to the national alcohol policy and define the message, illustration, size and duration of the display of the advertisement of alcoholic beverages on the internet, Facebook Instagram Line, in order to reduce the awareness of alcohol advertising on online media that will affect the attitude and non-drinking of children and youth and also omit the words in Section 32 of the Alcoholic Beverages Control Act, the words "which exaggerate properties or induce others to drink directly or indirectly" and prohibit the advertisement of alcoholic beverages due to the release of alcoholic beverages in various stores and the general public can easily buy products.